DAMPAK FILM NEGERI 5 MENARA TERHADAP KREATIVITAS MAHASISWA KOMUNIKASI PENYIARAN ISLAM UNIVERSITAS ISLAM INTERNASIONAL DARULLUGHAH WADDA’WAH PASURUAN - Rofiuddin, Mohammad; Achmad Zainul Hafid (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2021)
This research is focused on determining the communication carried out by Film Negeri 5 Menara. The purpose and usefulness of this study are to find out how the impact of creativity on students and the communication barriers experienced by Islamic Broadcasting Communication Students. This type of research uses a qualitative type of research using the Hypodermic Needle communication theory. The data collection techniques used in this study were interviews, observations, and documentation. Data analysis techniques in this qualitative research are carried out in several stages, namely data reduction, data presentation, and drawing conclusions. The results of this study are: sincerity embedded in students the nature of sincerity equipped with sincere intentions from the results of watching this film, Cooperation makes students willing to help in all things as a result of watching this film, shooting makes students imaginative and creative in producing a film work.